دور التدقيق الضريبي في اكتشاف التهرب الضريبي دراسة ميدانية في مديريات المال بمحافظة اللاذقية - الدالي سليمان; داؤد رواد (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يعد التدقيق الضريبي من أهم وسائل الإدارة الضريبية في التأكد من حقيقة الإيرادات الضريبية المتحققة, إذ إن الدور الذي يقوم به المدقق يكمن في كونه وسيلة، وليست غاية تهدف إلى خدمة الإدارة الضريبية في تحديد الوعاء الضريبي على نحو علمي منظم يحافظ على حقوق المكلفين والدولة جنباً إلى جنب بالإضافة إلى زيادة مستوى الالتزام بأحكام التشريع الضريبي والامتثال له، وتتجلى أهميتها بالتأكد من صحة ما جاء بدفاتر المكلفين من بنود الحسابات ويتحقق من جوانبها كافة لضمان سلامتها من حالات الغش والتهرب الضريبي. ويسعى هذا البحث إلى تبيان واقع إجراءات التدقيق الضريبي في الدوائر الضريبية في سورية وأثر ذلك على التهرب الضريبي, ولغرض الوصول للنتائج استخدم الباحث المنهج الوصفي التحليلي, وتم تصميم استبانة أداةً للدراسة، تم توزيعها على عينة من مراقبي الدخل ورؤساء الدوائر في مديريات المال بمحافظة اللاذقية ، حيث تكونت من 82 فرداً تم اختيارها بشكل عشوائي, وبعد الدراسة والتحليل تم التوصل إلى النتائج الآتية: 1- يتم القيام بعملية التخطيط لأعمال التدقيق من قبل الإدارة الضريبية قبل البدء بتلك العملية, حيث يوجد علاقة ارتباط طردية بين تخطيط التدقيق الضريبي وإمكانية اكتشاف التهرب الضريبي. 2- ضعف قيام بعض مراقبي الدخل بإجراءات التحقق من الدفاتر والسجلات المحاسبية وجمع عدد كافٍ من الأدلة والقرائن, يسهم في تخفيض تدعيم مصداقية التدقيق الضريبي, و تخفيض إمكانية اكتشاف التهرب الضريبي. 3- إعداد مراقب الدخل للتقرير النهائي بشكل يتضمن إِشارة واضحة إلى مدى انسجام القوائم المالية مع المبادئ المحاسبية المتعارف عليها, ومع مواد القانون الضريبي، وكذلك الالتزام بالمعايير المقبولة عموماً, يساعد في اكتشاف التهرب الضريبي. The tax audit of the most important means of tax administration to make sure of the fact that the tax revenue generated, as the role of the auditor is to being a means and not an end aimed at Tax Administration Service in determining the tax base as a scientific organizer maintains the assigned rights and the state along In addition to increasing the level of commitment to the provisions of tax legislation and compliance with, and reflected the importance of ensuring the accuracy of the books came in charge of the accounting items and checks of all aspects to ensure the integrity of cases of fraud and tax evasion. This research seeks to demonstrate the reality of the tax audit in tax circles in Syria and its impact on tax evasion procedures, for the purpose of access to the results, the researcher used descriptive analytical approach was to identify a tool for the study design, were distributed to a sample of income monitors and heads of departments in the districts money Latakia province where consisted of 82 individuals have been selected at random, and after the study and analysis was reached the following conclusions: 1- are doing the planning process for the audit by the tax administration before starting that process, where there is a positive correlation between the tax audit planning relationship and the ability to detect tax evasion. 2- weakness the income observer verification of accounting books and records and to collect sufficient number of evidence and clues procedures, contribute to the reduction of strengthening the credibility of the tax audit, thereby reducing the ability to detect tax evasion. 3- Prepare the income of the final report includes an observer in a clear reference to the extent to which the financial statements with generally accepted accounting principles, and with the tax law materials, as well as the commitment to generally accepted standards, help in the discovery of tax evasion.